2013
DOI: 10.1152/physiolgenomics.00087.2013
|View full text |Cite
|
Sign up to set email alerts
|

S49G and R389G polymorphisms of the β1-adrenergic receptor influence signaling via the cAMP-PKA and ERK pathways

Abstract: Zhang F, Steinberg SF. S49G and R389G polymorphisms of the ␤1-adrenergic receptor influence signaling via the cAMP-PKA and ERK pathways. Physiol Genomics 45: 1186-1192, 2013. First published October 22, 2013 doi:10.1152/physiolgenomics.00087.2013.-Two functionally important ␤ 1-adrenergic receptor (␤1AR) polymorphisms have been identified. The R389G polymorphism influences coupling to the Gs-cAMP pathway. R 389 -␤1ARs display enhanced activation of cAMP/PKA; they provide short-term inotropic support but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
(43 reference statements)
1
14
0
Order By: Relevance
“…Following Iso stimulation, ERK activation was assessed by phospho-ERK (p-ERK) immunoblotting. Consistent with previous studies ( Zhang and Steinberg, 2013 ; Copik et al. , 2015 ), Iso stimulation resulted in a significant increase in ERK activation.…”
Section: Resultssupporting
confidence: 92%
“…Following Iso stimulation, ERK activation was assessed by phospho-ERK (p-ERK) immunoblotting. Consistent with previous studies ( Zhang and Steinberg, 2013 ; Copik et al. , 2015 ), Iso stimulation resulted in a significant increase in ERK activation.…”
Section: Resultssupporting
confidence: 92%
“…Studies have also suggested that Ser49 undergoes less receptor internalization than the glycine variant, also resulting in greater downstream signalling. Data from the last 10–15 years and confirmed again in the past 2 years document that both the Ser49Gly and Arg389Gly variants are functional, although the effect of the Arg389Gly allele is greater and might obscure the functional effect of the codon 49 genotype 42 . The ancestral alleles (Ser49 and Arg389) are both associated with greater agonist-mediated effects than the variant alleles.…”
Section: Hypertension Pharmacogenomicsmentioning
confidence: 88%
“… 5 Several studies support the role of cyclic Adenosine Monophosphate (cAMP) in atherogenesis by modulating the function of vascular endothelium, the production of reactive oxygen species, the recruitment of circulating monocytes to the artery wall and their differentiation into macrophages-foam cells, by controlling the expression of pro-and anti-inflammatory interleukin, and regulating serum level of triglycerides and cholesterol. 6 , 7 cAMP is also a possible target for prevention and treatment of atherosclerosis. 6 The major non-synonymous SNPs of β2AR have been recognized at nucleotides 46 (A>G) (rs1042713) and 79 (C>G) (rs1042714) causing changes in amino acid residues at position 16 (Arg>Gly) and 27 (Gln>Glu) of the amino terminus respectively of the fourth intracellular loop.…”
Section: Introductionmentioning
confidence: 99%